The Effect Of Training And Human Resource Development On Employee Performance At The Penukal Utara District Office In Pali Regency - Amelia, Esti; Aryanti, Rahmi; Mario, Asma (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine the extent to which human resource training and development influenced employee performance at the Penukal Utara Sub-district Office, PALI Regency. This study used a quantitative approach with data collection techniques through surveys and interviews. The researcher distributed questionnaires to 45 respondents and conducted an interview with one of the employees at the sub-district office. The data obtained were then analyzed using multiple linear regression methods. The results of the analysis showed that training and development together had a significant influence on employee performance of 21.9%. Meanwhile, the rest was influenced by other factors such as motivation, work discipline, leadership style, and work environment. From the calculation results, it is known that the Fcount value of 7.161> Ftable of 2.01, with a significance value of 0.02 < 0.05. This indicates that H₀ is rejected and H₁ is accepted, so it can be concluded that training and development have a significant influence on employee performance.